Long term relationship between exports, gross domestic capital formation, transfer fund allocation, and private investment in Jambi Province - Sayid Syekh; Zainuddin Zainuddin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
This study investigates the relationship between Jambi export with gross domestic capital formation, allocation of transfer funds, and private investment, based on the Vector Error Correction Model (VECM). The results show that, both in the short and long term, the gross domestic capital formation, allocation of transfer funds, and private investment can explain changes in Jambi exports. The gross domestic capital formation strongly influences Jambi's export fluctuations compared to other variables. There is a disequilibrium relationship in the short term, and it becomes equilibrium in the long run. Only 69 percent of export changes can be determined in the current period, and the rest is determined in other periods. Likewise, the gross domestic capital formation, only 38 percent, can be determined in the current period, and the rest is determined in other periods. Based on the impulse response function, the impact of export shocks has a large impact on itself. Shocks have a very significant impact and have a long lead to stable levels. Shocks can cause changes in Jambi exports to gross domestic capital formation. Shocks to the formation of gross domestic capital formation require a long time to reach a stable level.